PECULIARITIES OF THE SYSTEM OF RELATIONS OF FEMALE CADETS OF HIGHER EDUCATIONAL ESTABLISHMENTS OF THE MINISTRY OF INTERNAL AFFAIRS AT DIFFERENT STAGES OF PROFESSIONAL TRAINING (Law and Safety, 2018)
The results of an empirical study of the system of relations of female cadets, which are trained at higher educational establishments of the Ministry of Internal Affairs, have been provided. To accomplish the study, we have used the technique of the color test of relations on the material of 73 concepts, which designate the objects and phenomena of the social and professional environment important for cadets: 1) a block of existential concepts; 2) a block of Ego-concepts; 3) a block of negative concepts; 4) a block of professional and learning-related concepts; 5) a block of emotional concepts; 6) a block of universal and national concepts. On the basis of the obtained matrices of rank positions of the concepts, we have built generalized semantic spaces of the system of relations of female cadets of the first and third years of training.The dynamics of the changes in relations of female cadets at different training courses has been provided in the form of a comparative table. As criteria for comparison, we have considered the generalized blocks “Attitude to oneself”, “Attitude to life”, “Attitude to educational and future professional activity”, “Attitude to the family”. The features and principal differences of the systems of relations of female cadets at different stages of professional training have been demonstrated.
Keywords: system of relations, personal relations, cadets of higher educational establishments of the Ministry of Internal Affairs.